What are the clinical features of lung cancer before the diagnosis is made? A population based case-control study. Issue 12 (14th October 2005) - Hamilton, W; Peters, T J; Round, A; Sharp, D
Abstract : Background: Over 38 000 new cases of lung cancer occur each year in the UK. Most are diagnosed after initial presentation to primary care, but the relative importance of the various clinical features is largely unknown. Methods: A population based case-control study was undertaken in all 21 general practices in Exeter, Devon, UK (population 128 700). 247 primary lung cancers were studied in subjects aged over 40 years diagnosed between 1998 and 2002 and 1235 controls matched by age, sex and general practice. The entire primary care record for 2 years before diagnosis was coded using the International Classification of Primary Care-2. Univariable and multivariable conditional logistic regression analyses were used to identify and quantify clinical features independently associated with lung cancer. The main outcome measures were odds ratios and positive predictive values for these variables. Results: Seven symptoms (haemoptysis, loss of weight, loss of appetite, dyspnoea, thoracic pain, fatigue and cough), one physical sign (finger clubbing), and two abnormal investigation results (thrombocytosis and abnormal spirometry) were associated with lung cancer in multivariable analyses, as was cigarette smoking. After excluding variables reported in the final 180 days before diagnosis, haemoptysis, dyspnoea and abnormal spirometry remained independently associated with cancer. Conclusions: This study provides an evidence base for selection of patients for investigation of possible lung cancer, both for clinicians and for developers of guidelines.